Impactos antrópicos no regime hidrológico de tributários do Rio Tocantins - Rodrigues, Jéssica Assaid Martins (2017)
Anthropic interference in the climatic system is one of the main responsible for the changes in hydrological regime in a certain region. Thus, understanding and modeling the relations between climate, water dynamics and landscape is of relevant importance for environmental planning and conservation. In this context, the objectives of this work was to simulate the hydrology and analyze the possible impacts of different climatic scenarios in the hydrological regime of the Palma (BHP), Manuel Alves da Natividade (BHMA) and Sono (BHS) hydrographic basins. For this, the calibration and validation of the SWAT hydrological model was sought over for the hydrographic basins in question and the hydrological impacts of climatic change over the representative concentration forcing RCP 4.5 and RCP 8.5 were simulated by regional models Eta-MIROC5 and Eta-HadGEM2-ES, over the XXI century. The SWAT model presented good performance in the calibration and validation phases, demonstrating the capacity of the model in adequately predicting the hydrological impacts derived of climatic changes. The simulations obtained from the SWAT model coupled with the Eta-HadGEM2-ES and Eta-MIROC5 for RCPs 4.5 and 8.5 indicated the reduction of runoff for all applications, with more critical results obtained with RCP 8.5, especially in the Eta-HadGEM2-ES model, for the end of the XXI century. Thus, serious issues can occur in the future in terms of water availability for the studied region, affecting many segments of society, such as water supply for consumption, agriculture and hydroelectric use.